CERRAHİ YENİDOĞAN YOĞUN BAKIM ÜNİTESİNDE SEPSİS OLGULARININ DEĞERLENDİRİLMESİ - AKOVA, Fatih; İLÇE, Zekeriya; KÖKSAL, Fatma; CELAYİR, Sinan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- In surgical neonatal intensive care units nosocomial infections and septicemia are still the leading cause of neonatal mortality. In our study 489 cases extending a period of 5 years was investigated retrospectively. Results.- 35.5% had clinical septicemia and in this group 76% had hemoculture positive septicemia. The mortality rate was 53%. In the first years, Enterobacteriaceae, Coagulase negative Staphylococci, Stenotrophomonas maltophilia sp. and Candida sp. Are mostly encountered but in recent years MRSA, Pseudomonas sp, Enterobacter sp. are most common microorganisms. Although antibiotic resistance in some resistant microorganism are seen more frequently, in our series we had a remarkable decrease in septicemia and related mortality. Conclusion.- As the intense use of modern technology in neonatal surgical intensive care units improved the fight against neonatal septicemia, neonatal mortality is still due to nosocomial infections and septicemia.